Effect of Obesity on Histamine-Induced Asthma in Young Population - Abdul Majid ,Inam-ul-Haq ,Muhammad Amer Saleem ,Hamza Hassan (Journal of Rawalpindi Medical College, 2013)
Background: To determine relationship of histamine-induced asthma with obesity. Methods: Sixty healthy young subjects were included in the study. Histamine challenge test was given after obtaining consent. A definitive criterion of 13-15% decrease in FEV1 and 15-20% decrease in PEFR was outlined to term a histamine test positive, i.e., histamine-induced asthma (HIA). Body mass index (BMI) was evaluated for each subject using the height and weight. Results were obtained after calculations and noting down the percentage fall in reference to the baseline value. An inter-group comparison was afterwards undertaken. Results: Mean age of the subjects included in our study was 19.69 ±0.15years and mean BMI calculated was 23.50±2.10 kg/m2. The subjects were then categorized as those having normal BMI and those with high BMI (overweight category). A total of 18 subjects were HIA positive with 09 being normal and 09 overweight. Among the 42 HIA negative subjects, 25 were normal and 17 were overweight. After statistical analysis, p-value was observed to be morre than 0.05 (statistically insignificant). Conclusion: Relationship of obesity, with the development of an exacerbated attack of asthma or with the severity and termination of an attack of asthma, is not ascertained